Dairy Business Analysis Project: Financial Summary for 1995-2001 - Albert de Vries; Russell Giesy; Lane Ely; A. de Araujo; Andy Andreasen; Brent Broaddus; Shepard Eubanks; Doug Mayo; P. Miller; T. Seawright; Christopher Vann (EDIS, 2004)
Financial data for the years 1995 through 2001 were collected from participating dairies and screened for completeness and validity. Each dairy then received a report detailing its financial results compared to the average results for the other participants and the dairies with the highest net farm income from operations per cwt. This publication is a summary of the data collected for the years 1995 through 2001. Some results may be slightly different from the annual DBAP summaries published in EDIS because minor changes in the calculations have been made over the years. This publication is intended for general use by dairy farmers, the allied industry, and government, and educational professionals. This document is DS174, one of a series of the Department of Animal Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published July 2003.